The impacts of sustainable industrial revolution (IR) on the profitability of Hungarian food companies - Máté, Domicián; Oláh, Judit; Erdei, Edina; Estiyanti, Ni Made; Bács, Zoltán; Kovács, Sándor (Frontiers in Sustainable Food Systems, 2022)
There is growing literature on the concept and objectives of corporate sustainability (CS), but less attention is paid to a comprehensive approach to economic, social and ecological factors and industrial revolution (IR). Specifically, this paper contributes to the academic debate on the relationship between CS and IR in agri-food economics using firm-level data. The study used quantitative pathway models to measure the extent to which technologies affect the development of social, ecological and economic factors in Hungarian food manufacturing companies. The research was conducted using partial least squares path modeling (PLS-PM) and categorical principal component analysis (CATPCA) to calculate the direct and indirect effects of IR technologies on profitability outcomes. This study has shown that the livable and sustainable path hypotheses can be confirmed. Consequently, the food manufacturing businesses whose managers think along the viable and sustainable lines tend to be more profitable. However, the ecological and economic factors strengthened the positive impact of the social dimension on food corporate profitability. Decision-makers should not wait for a pie in the sky for emerging sustainability but consciously embrace the CS issues that only provide a direction for the changes.